A lithium-ion cylindrical battery and an electrical device

By using tungsten trioxide in situ to modify fluorine-doped multi-walled carbon nanotubes as conductive agents in lithium-ion batteries, the problem of insufficient conductivity of lithium iron phosphate electrons is solved, and the rapid charging and discharging and long-cycling performance of the battery are improved.

CN118867240BActive Publication Date: 2025-07-18JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410832601.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2025-07-18
Estimated Expiration
2044-06-26

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, lithium iron phosphate has poor electronic conductivity, which limits its fast charging and discharge performance, and the physical mixing effect of traditional conductive agents is poor.

Method used

Tungsten trioxide in situ modified fluorine-doped multi-walled carbon nanotubes (WO3/F-MWCNTs) as composite conductive agents are used for the positive electrode coating of lithium-ion cylindrical batteries. They are prepared by thermal evaporation and carbon nanotube growth technology to form uniformly distributed tungsten trioxide particles to improve conductivity.

Benefits of technology

It improves the chemical stability and cycling performance of the positive electrode material, enhances the fast charging and fast release and long circulation performance of the battery, and improves the charging and discharging rate and magnification capacity maintenance performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118867240B_ABST
    Figure CN118867240B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries, and discloses a lithium-ion cylindrical battery and an electrical device, comprising: a positive electrode sheet, a negative electrode sheet, and a separator located therebetween; the positive electrode sheet includes a positive electrode current collector and a positive electrode coating located on at least one surface of the positive electrode current collector; wherein the positive electrode coating includes a positive electrode active material, a composite conductive agent, and a binder; the composite conductive agent includes tungsten trioxide in-situ modified fluorine-doped multi-walled carbon nanotubes. By introducing tungsten trioxide into the positive electrode conductive agent, the chemical stability and cycling performance of the positive electrode material are improved. The octahedral molecular unit along the c-axis in the WO3 crystal structure is beneficial to electron conduction, and at the same time, the continuous three- and six-ring tunnels constructed along the ab plane in the WO3 crystal structure are beneficial to ion diffusion, which helps to improve the charge and discharge rate, power density, and rate capacity retention performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and particularly relates to a lithium-ion cylindrical battery and an electrical device. Background Art

[0002] Lithium iron phosphate (LiFePO4) is considered a very promising cathode material for lithium-ion batteries due to its high theoretical capacity, excellent cycle stability, and environmental friendliness. However, the poor electronic conductivity of LFP limits its fast charge and discharge performance in batteries. Traditional conductive agents, such as carbon black, acetylene black, and graphene, can form composites with LFP through physical mixing to improve its electron transfer rate. However, simple physical mixing often cannot achieve the best conductive effect because of the differences in the interfacial contact between different conductive agents and LFP and the constructed conductive network.

[0003] Therefore, it is necessary to develop a lithium-ion battery with a new type of highly efficient and low-cost conductive agent to solve the problem of insufficient conductivity between the conductive agent and LFP in lithium-ion batteries. Summary of the Invention

[0004] The object of the present invention is to provide a lithium-ion cylindrical battery, a preparation method of a composite conductive agent, multi-walled carbon nanotubes, a positive electrode coating, and an electrical device.

[0005] The technical solution of the present invention is as follows:

[0006] A lithium-ion cylindrical battery, comprising: a positive electrode sheet, a negative electrode sheet, and a separator located between the two; the positive electrode sheet includes a positive electrode current collector and a positive electrode coating located on at least one surface of the positive electrode current collector; wherein the positive electrode coating includes a positive electrode active material, a composite conductive agent, and a binder; the composite conductive agent includes tungsten trioxide in-situ modified fluorine-doped multi-walled carbon nanotubes (WO3 / F-MWCNTs).

[0007] Further, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate.

[0008] Further, the lithium nickel cobalt manganese oxide material includes one or more of a high-nickel ternary lithium nickel cobalt manganese oxide material or a medium-nickel ternary lithium nickel cobalt manganese oxide material; the chemical formula of the high-nickel lithium nickel cobalt manganese oxide material is Li a Ni x Co y Mn z M bO₂, where 0.9 < a < 1.1, 0.7 < x ≤ 0.94, 0.1 ≤ y < 0.4, 0.05 ≤ z < 0.4, 0 ≤ b ≤ 0.1, and M is a combination of any one or more of Al, Mg, Zr, Ti, W, Nb, Mo, and B. The chemical formula of the medium-nickel ternary lithium nickel cobalt manganate material is Li a Ni x Co y Mn z M b O₂, where 0.9 < a < 1.1, 0.4 ≤ x ≤ 0.7, 0.1 ≤ y < 0.4, 0.05 ≤ z < 0.4, 0 ≤ b ≤ 0.1, and M is a combination of any one or more of Al, Mg, Zr, Ti, W, Nb, Mo, and B.

[0009] Furthermore, the lithium-ion cylindrical battery satisfies at least one or more of the following conditions: (1) The average particle size Dv50 of the tungsten trioxide is 9 - 60 nm; (2) The molar ratio of tungsten trioxide to silicon in the positive electrode sheet to that in the negative electrode sheet is n(WO₃) / n(Si) = 0.01 - 0.05; (3) The resistivity R of the positive electrode sheet is 0.7 - 3.7 Ω·cm; (4) The mass fraction of fluorine element in the composite conductive agent is 0.5 - 1.5%; (5) The aspect ratio of the multi-walled carbon nanotubes in the composite conductive agent is (600 - 1400):1.

[0010] Furthermore, the negative electrode coating includes a negative electrode active material, a conductive agent, and a binder. The negative electrode active material includes a mixture of at least two of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-carbon material, and silicon-oxygen material, and the silicon content in the negative electrode active material is 5 - 40 wt%.

[0011] Furthermore, the negative electrode active material is a graphite negative electrode with a high silicon content, and the molar ratio of tungsten trioxide in the positive electrode to silicon in the negative electrode is n(WO₃) / n(Si) = 0.01 - 0.02, preferably n(WO₃) / n(Si) = 0.01443.

[0012] Furthermore, the diameter of the lithium-ion cylindrical battery is 30 - 50 mm, and the height is 70 - 180 mm; and the ratio of the height to the diameter is greater than 1.6.

[0013] Furthermore, the charging process of the lithium-ion cylindrical battery includes the following steps:

[0014] a. Constant current charging to 80% of the nominal voltage of the battery;

[0015] b. Switch to constant voltage charging until the charging current drops to the set cut-off current value.

[0016] Further, the discharging process of the lithium-ion cylindrical battery includes the following steps:

[0017] a. Constant current discharge to 20% of the nominal voltage of the battery;

[0018] b. The discharge current remains unchanged or varies within a preset current range during the discharging process.

[0019] Further, the lithium-ion cylindrical battery supports fast charging and fast discharging functions, with a charging time less than 0.6 hours and a discharging time less than 1 hour.

[0020] Further, after 600 cycles under fast charging and fast discharging conditions, the capacity retention rate of the lithium-ion cylindrical battery is not less than 80%.

[0021] Another technical solution of the present invention is:

[0022] A preparation method of a composite conductive agent used in a lithium-ion cylindrical battery as described above, comprising the following steps:

[0023] (1) Pretreat the substrate: Using a silicon dioxide silicon wafer as the substrate, deposit a 0.3 - 1 nm gold thin film layer on the substrate by thermal evaporation to obtain a gold thin film silicon wafer, and perform ethanol cleaning and heat pretreatment on it to obtain a pretreated substrate;

[0024] (2) Synthesize fluorine-doped multi-walled carbon nanotubes: Select a catalyst, introduce a carbon source while introducing a fluorine source as a doping source; at the same time, control the flow rates of the carrier gas and the carbon source gas; control the growth time of the carbon nanotubes, take out the carbon nanotubes grown on the pretreated substrate, obtain a suspension through pickling and ultrasonic treatment, and then filter, wash and dry the suspension to remove residual catalysts and by-products to obtain fluorine-doped multi-walled carbon nanotubes (F-MWCNTs);

[0025] (3) In-situ growth of tungsten trioxide WO3 metal nanoparticles inside the carbon nanotubes: Mix the metal alkoxide precursor with a solvent, heat and stir to promote the hydrolysis reaction of the metal alkoxide. After hydrolysis is completed, a sol is obtained. Add the fluorine-doped multi-walled carbon nanotubes (F-MWCNTs) to the sol; remove most of the solvent (ethanol or propanol) by vacuum drying (80 °C, 100 Pa) to form a dry gel; perform heat treatment on the dry gel at a high temperature to promote the final crystallization and growth of tungsten trioxide WO3 particles to obtain tungsten trioxide in-situ modified fluorine-doped multi-walled carbon nanotubes (WO3 / F-MWCNTs).

[0026] Further, the particle size of the tungsten trioxide is 10 - 50 nm, and it is evenly distributed on the surface of the fluorine-doped multi-walled carbon nanotubes (F-MWCNTs).

[0027] Further, the mass ratio of the fluorine-doped multi-walled carbon nanotubes (F-MWCNTs) to the tungsten trioxide is 95:5 to 90:10.

[0028] Further, the catalyst is a transition metal and its oxides and carbides, including any one or more of iron, cobalt, and nickel.

[0029] Further, the carbon source includes any one or more of methane, acetylene, ethylene, and carbon monoxide.

[0030] Further, the fluorine source includes any one or more of fluorine gas, nitrogen trifluoride, and carbon tetrafluoride.

[0031] Further, the carrier gas is nitrogen.

[0032] Further, the metal alkoxide precursor is tetrabutyl titanate (TBT) or ethyl titanate.

[0033] Further, in the step S1, it also includes: cleaning the silica wafer by ultrasonic cleaning and chemical treatment to remove surface contaminants; and the thermal evaporation method specifically is: placing the gold material with a purity of 99.99% on an electron beam heater, heating to 1100 - 1300 °C to evaporate gold to deposit it on the cleaned silica wafer; immersing the gold-containing thin film wafer in ethanol, and the ethanol cleaning and heating pretreatment specifically is: ultrasonic cleaning for 5 minutes, and heating to 170 - 210 °C in a nitrogen atmosphere and maintaining for 10 minutes to remove ethanol residues and activate the surface; the deposition environment is high vacuum, and the vacuum degree is 95 kPa.

[0034] Further, in the step S2: the pickling specifically is: pickling the grown carbon nanotubes with a dilute hydrochloric acid solution to remove residual catalysts; the ultrasonic treatment specifically is: ultrasonic treatment for 25 - 35 minutes to disperse the carbon nanotubes; the filtration, washing, and drying specifically is: filtering the suspension with a polytetrafluoroethylene filter, then washing with deionized water, and drying the carbon nanotubes at 60 - 80 °C for 10 - 12 hours.

[0035] Another technical solution of the present invention is:

[0036] Tungsten trioxide in-situ modified fluorine-doped multi-walled carbon nanotubes prepared by the preparation method as described above.

[0037] Another technical solution of the present invention is:

[0038] A positive electrode coating, and the preparation method of the positive electrode coating includes: using in-situ modified tungsten trioxide on fluorine-doped multi-walled carbon nanotubes as a composite conductive agent, mixing it with a positive electrode active material and a binder, and dissolving them in deionized water to form a positive electrode slurry with a solid content of 40-60 wt%, coating the positive electrode slurry on a current collector, drying and heat-treating to obtain the positive electrode coating; wherein the mass ratio of the positive electrode active material, the composite conductive agent, and the binder is (96-98%):(1-3%):(1-3%).

[0039] Another technical solution of the present invention is:

[0040] An electrical device includes the lithium-ion cylindrical battery as described above.

[0041] The present invention provides a lithium-ion cylindrical battery and an electrical device, and the beneficial effects are:

[0042] 1. The introduction of tungsten trioxide improves the chemical stability and cycling performance of the positive electrode material. The octahedral molecular units along the c-axis in the WO3 crystal structure are beneficial to electron conduction, which has a positive impact on the charge and discharge efficiency and power density of the battery. The continuous three- and six-ring tunnels constructed along the ab plane in the WO3 crystal structure are beneficial to ion diffusion, which helps to improve the charge and discharge rate and rate capacity retention performance of the battery;

[0043] 2. It improves the electronic conductivity of the positive electrode material and can enhance the fast charge and discharge and long cycling performance of the battery. Description of the Drawings

[0044] Figure 1 Shows the assembly schematic diagram of the outer shell and the positive and negative electrodes of the lithium-ion cylindrical battery involved in some embodiments;

[0045] Figure 2 Shows the coating schematic diagram of the positive electrode sheet of the lithium-ion cylindrical battery involved in some embodiments;

[0046] Figure 3 Shows the coating schematic diagram of the negative electrode sheet of the lithium-ion cylindrical battery involved in some embodiments;

[0047] Figure 4 Shows the comparison diagram of the 1C discharge capacity cycle life of Example 1 and Comparative Example 1 of the lithium-ion cylindrical battery involved in some embodiments.

[0048] In the figure:

[0049] 1. Outer shell; 2. Positive electrode end; 3. Negative electrode end; 20. Positive electrode column; 21. Positive electrode coating area; 22. Uncoated area of the positive electrode; 31. Negative electrode coating area; 32. Uncoated area of the negative electrode. Detailed Embodiments

[0050] The present invention designs a lithium-ion cylindrical battery, which is composed of a positive electrode sheet, a negative electrode sheet, and a separator located therebetween; the positive electrode sheet includes a positive electrode current collector and a positive electrode coating located on at least one surface of the positive electrode current collector; the negative electrode sheet includes a negative electrode current collector and a negative electrode coating located on at least one surface of the negative electrode current collector; wherein the positive electrode coating includes a positive electrode active material, a composite conductive agent, and a binder; the composite conductive agent includes tungsten trioxide in-situ modified fluorine-doped multi-walled carbon nanotubes (WO3 / F-MWCNTs); the positive electrode active material can be one or more of lithium nickel cobalt manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate; the negative electrode coating is composed of a negative electrode active material, a conductive agent, and a binder, and the negative electrode active material can be at least two mixtures of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-carbon material, and silicon-oxygen material; preferably, the negative electrode active material is a graphite negative electrode with a high silicon content, the silicon content in the negative electrode active material is 5-40 wt%, and the molar ratio of tungsten trioxide in the positive electrode to silicon in the negative electrode is n(WO3) / n(Si)=0.01-0.05, preferably n(WO3) / n(Si)=0.01-0.02. If n(WO3):n(Si)<0.01, WO3 cannot reach the expected effect value, while if n(WO3):n(Si)>0.02, WO3 agglomeration, positive electrode sheet material loss, and lithium deposition on the negative electrode during battery operation will occur, which has an adverse effect on battery assembly and operation.

[0051] The preparation method of the composite conductive agent includes the following steps:

[0052] (1) Pretreat the substrate:

[0053] Using a silicon dioxide silicon wafer as the substrate, deposit a 0.3-1 nm gold thin film layer on the substrate by thermal evaporation to obtain a gold thin film silicon wafer, and perform ethanol cleaning and heat pretreatment on it;

[0054] (2) Synthesize fluorine-doped multi-walled carbon nanotubes:

[0055] Select a suitable catalyst, such as transition metals such as iron (Fe), cobalt (Co), nickel (Ni), etc., or their oxides or carbides. Introduce a carbon-containing gas, such as methane (CH4), acetylene (C2H2), ethylene (C2H4), or carbon monoxide (CO), etc., into the reactor as the carbon source for the growth of carbon nanotubes. While introducing the carbon source, introduce the selected fluorine source gas, such as fluorine gas (F2), nitrogen trifluoride (NF3), carbon tetrafluoride (CF4), etc., as the doping source; at the same time, control the flow rates of the carrier gas (such as argon Ar or nitrogen N2) and the carbon source gas to maintain appropriate reaction conditions;

[0056] Under the action of high temperature and catalyst, the carbon source gas decomposes, and carbon atoms deposit on the surface of the catalyst and gradually form carbon nanotubes. The carbon nanotubes grown on the pretreated substrate are taken out, and a suspension is obtained through pickling and ultrasonic treatment. Then, the suspension is filtered, washed, and dried to remove the residual catalyst and by-products, obtaining fluorine-doped multi-walled carbon nanotubes (F-MWCNTs).

[0057] (3) In-situ growth of WO3 metal nanoparticles inside carbon nanotubes:

[0058] A metal alkoxide precursor (such as tetrabutyl tungstate (TBT) or ethyl tungstate) and a solvent (such as ethanol or propanol) are heated and stirred to promote the hydrolysis reaction of the metal alkoxide. During the hydrolysis process, the metal alkoxide decomposes to form primary particles of metal oxide; after the hydrolysis is completed, fluorine-doped multi-walled carbon nanotubes (F-MWCNTs) are added to the sol; most of the solvent is removed to form a xerogel; the xerogel is heat-treated (sintered) at high temperature to promote the final crystallization and growth of WO3 particles. During the heat treatment process, the organic components are burned off, and uniformly distributed WO3 particles are formed on the surface of F-MWCNTs. Tungsten trioxide in-situ modified fluorine-doped multi-walled carbon nanotubes (WO3 / F-MWCNTs) are obtained.

[0059] The cylindrical battery includes a wound core composed of a positive and negative electrode plate and a separator of a cylindrical battery with a high capacity retention rate design, positive and negative current collectors, insulating sheets, a housing, and a cap. At the upper and lower ends of the wound core of the cylindrical battery with a high energy density design, a positive electrode tab and a negative electrode tab are respectively provided. The cylindrical wound core is connected to the negative current collector by welding, the negative current collector is connected to the housing by welding, the wound core is connected to the positive current collector by welding, an insulating sheet is placed on the positive current collector, and the positive current collector is connected to the cap by welding. The cap is connected to the housing by a rolling groove. Please refer to Figure 1 , a housing is provided around the cylindrical wound core, and a positive electrode post and a negative electrode post are respectively provided at the upper and lower ends. In the above structure, the tabs can be single, multiple tabs, or full tabs, preferably full tabs, and its housing can be a steel shell or an aluminum shell. The diameter of the cylindrical battery is 20 - 50 mm, the height is 60 - 150 mm, and the ratio of height to diameter is greater than 1.6.

[0060] Please refer to Figure 2 , the positive electrode plate includes a positive current collector and a positive electrode coating coated on at least one surface of the positive current collector. The positive current collector includes a coated area and an uncoated area. At least a part of the uncoated area of the positive electrode serves as a positive electrode tab, and the uncoated area of the positive electrode accounts for 1 - 10% of the area of the positive current collector.

[0061] Please refer to Figure 3, the negative electrode sheet includes a negative electrode current collector and a negative electrode coating coated on at least one surface of the negative electrode current collector. The negative electrode current collector includes a coated area and an uncoated area. At least a part of the uncoated area of the negative electrode serves as a negative electrode tab, and the uncoated area of the negative electrode accounts for 2-11% of the area of the negative electrode current collector.

[0062] To make the above objects, features, and advantages of the present invention more obvious and understandable, the technical solutions of the present invention will be further described below in conjunction with embodiments. However, the present invention is not limited to the listed embodiments, and should also include any other well-known changes within the scope of the rights required by the present invention.

[0063] As used herein, an "embodiment" or "embodiments" refers to specific features, structures, or characteristics that may be included in at least one implementation of the present invention. The phrase "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment that is mutually exclusive with other embodiments.

[0064] Test battery preparation method:

[0065] 1. Positive electrode sheet manufacturing method:

[0066] The positive electrode sheet includes a positive electrode current collector aluminum foil and a positive electrode coating coated on both surfaces of the aluminum foil; wherein, calculated by weight percentage, the positive electrode coating includes 97% lithium nickel cobalt manganate (811 positive electrode), 0.4% single-walled carbon nanotube conductive agent, 1.6% conductive agent, and 1% polyvinylidene fluoride PVDF binder. The above substances are added to NMP and stirred to form a positive electrode slurry with a solid content of 60%, which is coated on the positive electrode current collector to form a positive electrode sheet;

[0067] 2. Negative electrode manufacturing method:

[0068] The negative electrode sheet includes a negative electrode current collector copper foil and a negative electrode coating coated on both surfaces of the copper foil. Calculated by weight percentage, the negative electrode coating includes 96% artificial graphite, 1.0% conductive agent acetylene black, 1% thickener CMC, and 2% negative electrode binder polyacrylate LA133. The above substances are added to deionized water and stirred to form a negative electrode slurry with a solid content of 40%, which is coated on the negative electrode current collector to form a negative electrode sheet.

[0069] 3. Electrolyte:

[0070] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0071] 4. Separator:

[0072] The separator includes a high-porosity power separator. The base film is made of PE with a thickness of 9 μm, and the ceramic coatings on both sides have a thickness of 1 μm, and the PVDF coating has a thickness of 1 μm. The air permeability of the separator is ≥ 100 s / 100 mL.

[0073] 5. Assembly:

[0074] After the positive electrode sheet and the negative electrode sheet are respectively roll-pressed, slit, and die-cut, they are wound simultaneously with the separator to obtain a 21700 cylindrical battery core. After welding the battery core to the electrical connection sheet, it is placed into the battery case. After completing the processes of liquid injection, sealing, and formation, an experimental battery is obtained.

[0075] Example 1. This example demonstrates a preparation method of a lithium-ion cylindrical battery according to the following steps.

[0076] Using a silicon dioxide silicon wafer as the substrate, a 1-nm gold thin film layer is deposited on the substrate by thermal evaporation to obtain a gold thin film silicon wafer, which is then cleaned with ethanol and preheated. Select Fe2O3 as the catalyst, and introduce acetylene (C2H2) into the reactor as the carbon source for the growth of carbon nanotubes. While introducing the carbon source, nitrogen trifluoride (NF3) is introduced as the doping source. By controlling the gas injection time and flow rate, fluorine-doped multi-walled carbon nanotubes (F-MWCNTs) are obtained. In this example, the pore diameter of the carbon nanotubes is 7 nm and the length is 7 μm, so the aspect ratio is 1000 / 1, and the doping amount of fluorine element in the carbon nanotubes is 1 wt.%.

[0077] 10 g of tetrabutyltungstate (TBT) and 65 g of propanol are heated and stirred to promote the hydrolysis reaction of the metal alkoxide. After hydrolysis is completed, 95 g of F-MWCNTs are added to the sol, and after stirring for 1 h, most of the solvent is removed to form a dry gel. The dry gel is heat-treated (sintered) at 450 °C to promote the final crystallization and growth of WO3 particles. By controlling the amount of TBT and the heat treatment temperature, tungsten trioxide in-situ modified fluorine-doped multi-walled carbon nanotubes (WO3 / F-MWCNTs) with a WO3 content of 5 wt.% are obtained.

[0078] Using WO3 / F-MWCNTs as the positive electrode conductive agent, it is mixed with the positive electrode active material and the binder to form a positive electrode slurry, which is coated on the current collector, dried, and heat-treated to obtain the positive electrode of the lithium-ion battery.

[0079] The positive electrode sheet, the negative electrode sheet, and the separator are wound by a winding machine to form a core. The core is cut and stacked with the positive electrode tab and the negative electrode tab. Then, the positive electrode current collector and the negative electrode current collector are respectively welded to the core, and then the negative electrode current collector is welded to the steel shell. An insulating sheet is placed above the positive electrode current collector, and the positive electrode current collector is welded to the cap. Then, grooving, liquid injection, and sealing are completed to obtain a cylindrical battery.

[0080] The relevant parameter settings involved in this embodiment are as shown in Table 1 below:

[0081] Table 1 Relevant Parameters of Embodiment 1

[0082]

[0083] Embodiment 2: The method of this embodiment is the same as that of Embodiment 1, except that the doping amount of WO3 in the conductive agent is 3 wt.%, and at this time, n(WO3):n(Si) ≈ 0.01012.

[0084] Embodiment 3: The method of this embodiment is the same as that of Embodiment 1, except that the doping amount of WO3 in the conductive agent is 6 wt.%, and at this time, n(WO3):n(Si) ≈ 0.01864.

[0085] Embodiment 4: The method of this embodiment is the same as that of Embodiment 1, except that the D50 particle size of WO3 is 40 nm.

[0086] Embodiment 5: The method of this embodiment is the same as that of Embodiment 1, except that the D50 particle size of WO3 is 10 nm.

[0087] Embodiment 6: The method of this embodiment is the same as that of Embodiment 1, except that the D50 particle size of WO3 is 50 nm.

[0088] Embodiment 7: The method of this embodiment is the same as that of Embodiment 1, except that the doping amount of fluorine in the conductive agent is 0.5 wt.%.

[0089] Embodiment 8: The method of this embodiment is the same as that of Embodiment 1, except that the doping amount of fluorine in the conductive agent is 0.8 wt.%.

[0090] Embodiment 9: The method of this embodiment is the same as that of Embodiment 1, except that the doping amount of fluorine in the conductive agent is 1.5 wt.%.

[0091] Embodiment 10: The method of this embodiment is the same as that of Embodiment 1, except that the aspect ratio of carbon nanotubes in the conductive agent is 700:1.

[0092] Embodiment 11: The method of this embodiment is the same as that of Embodiment 1, except that the aspect ratio of carbon nanotubes in the conductive agent is 1300:1.

[0093] Embodiment 12: The method of this embodiment is the same as that of Embodiment 1, except that the carbon source introduced is methane gas.

[0094] Embodiment 13: The method of this embodiment is the same as that of Embodiment 1, except that the carbon source introduced is ethylene gas.

[0095] Example 14. The method of this example is the same as that of Example 1, except that the carbon source introduced is carbon monoxide gas.

[0096] Example 15. The method of this example is the same as that of Example 1, except that the fluorine source introduced is fluorine gas.

[0097] Example 16. The method of this example is the same as that of Example 1, except that the fluorine source introduced is carbon tetrafluoride gas.

[0098] Example 17. The method of this example is the same as that of Example 1, except that the mass fraction of the conductive agent in the positive electrode active material is 1 wt.%.

[0099] Example 18. The method of this example is the same as that of Example 1, except that the mass fraction of the conductive agent in the positive electrode active material is 3 wt.%.

[0100] Example 19. The method of this example is the same as that of Example 1, except that the positive electrode sheet material is lithium iron phosphate, and the negative electrode sheet material is 90% by mass of artificial graphite + 10% by mass of silicon carbide.

[0101] Example 20. The method of this example is the same as that of Example 1, except that the positive electrode sheet material is lithium iron phosphate, and the negative electrode sheet material is 95% by mass of artificial graphite + 5% by mass of silicon oxide.

[0102] Example 21. The method of this example is the same as that of Example 1, except that the positive electrode sheet active material is medium-nickel nickel cobalt manganese lithium oxide material LiNi 0.5 Co 0.2 Mn 0.3 O2.

[0103] Example 22. The method of this example is the same as that of Example 1, except that the positive electrode sheet active material is lithium nickel manganate LiNi 0.6 Mn 0.4 O2.

[0104] Example 23. The method of this example is the same as that of Example 1, except that the positive electrode sheet active material is lithium iron manganese phosphate LiFe 0.8 Mn 0.2 PO4.

[0105] Example 24. The method of this example is the same as that of Example 1, except that the positive electrode sheet active material is high-nickel nickel cobalt manganese lithium oxide material LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0106] Example 25. The method of this example is the same as that of Example 1, except that the cathode active material is a high-nickel lithium nickel cobalt manganate material LiNi 0.8 Co 0.1 Mn 0.1 O2 and a medium-nickel lithium nickel cobalt manganate material LiNi 0.5 Co 0.2 Mn 0.3 O2, and the mass ratio of the two is 9:1.

[0107] Comparative Example 1

[0108] The method of this comparative example is the same as that of Example 1, except that the selected conductive agent is CNTs.

[0109] Comparative Example 2

[0110] The method of this comparative example is the same as that of Example 1, except that the selected conductive agent is SP.

[0111] Comparative Example 3

[0112] The method of this comparative example is the same as that of Example 1, except that WO3 doping is not performed.

[0113] Comparative Example 4

[0114] The method of this comparative example is the same as that of Example 1, except that the doping amount of WO3 in the conductive agent is 2.5 wt.%, and at this time n(WO3):n(Si)≈0.00811.

[0115] Comparative Example 5

[0116] The method of this comparative example is the same as that of Example 1, except that the doping amount of WO3 in the conductive agent is 7 wt.%, and at this time n(WO3):n(Si)≈0.02137.

[0117] Comparative Example 6

[0118] The method of this comparative example is the same as that of Example 1, except that the particle size D50 of WO3 is 100 nm.

[0119] Comparative Example 7

[0120] The method of this comparative example is the same as that of Example 1, except that the doping amount of fluorine in the conductive agent is 2 wt.%.

[0121] Comparative Example 8

[0122] The method of this comparative example is the same as that of Example 1, except that the conductive agent is not doped with fluorine.

[0123] Comparative Example 9

[0124] This comparative example is the same as the method of Example 1, except that the aspect ratio of the carbon nanotubes in the conductive agent is 1500:1.

[0125] Comparative Example 10

[0126] This comparative example is the same as the method of Example 1, except that the aspect ratio of the carbon nanotubes in the conductive agent is 500:1.

[0127] Comparative Example 11

[0128] This comparative example is the same as the method of Example 1, except that no conductive agent is added to the positive active material.

[0129] Comparative Example 12

[0130] This comparative example is the same as the method of Example 1, except that the molar ratio of tungsten trioxide in the positive electrode sheet to silicon in the negative electrode is n(WO3) / n(Si) = 0.005.

[0131] Comparative Example 13

[0132] This comparative example is the same as the method of Example 1, except that the molar ratio of tungsten trioxide in the positive electrode sheet to silicon in the negative electrode is n(WO3) / n(Si) = 0.05.

[0133] Comparative Example 14

[0134] This comparative example is the same as the method of Example 1, except that the molar ratio of tungsten trioxide in the positive electrode sheet to silicon in the negative electrode is n(WO3) / n(Si) = 0.002.

[0135] Comparative Example 15

[0136] This comparative example is the same as the method of Example 1, except that the molar ratio of tungsten trioxide in the positive electrode sheet to silicon in the negative electrode is n(WO3) / n(Si) = 0.3.

[0137] Table 2 Experimental conditions of Examples 1 - 24 and Comparative Examples 1 - 13

[0138]

[0139]

[0140]

[0141] When the molar ratio of tungsten trioxide in the positive electrode to silicon in the negative electrode, n(WO3) / n(Si), is less than 0.01, the function of the composite conductive agent cannot be exerted, the resistivity of the electrode sheet is too high, the battery resistance is too large, and finally the battery discharge efficiency is reduced. When the molar ratio of tungsten trioxide in the positive electrode to silicon in the negative electrode, n(WO3) / n(Si), is higher than 0.1, the viscosity of the electrode paste is too high, the processing performance of the electrode sheet becomes poor, and at the same time, there will be a phenomenon of material dropping during the operation of the battery, which affects the battery safety and also reduces the battery cycle performance.

[0142] The test method for n(WO3) / n(Si) is as follows: perform cross-sectional CP EDS scans on the positive electrode sheet and the negative electrode sheet respectively, select a region range of 500 primary particles horizontally and 400 primary particles vertically, and perform EDS scan tests within this range to obtain the amounts of n(WO3) and n(Si).

[0143] The test method for the fluorine element proportion is to obtain a diffraction pattern by using XRD scanning, and perform quantitative analysis and calculation of the diffraction angle and peak intensity on the pattern to obtain the fluorine element proportion in the positive electrode conductive agent.

[0144] The test method for resistivity is as follows: take a certain number of positive electrode sheets and directly test the overall resistivity of the electrode sheets by the four-probe method.

[0145] Perform capacity performance evaluation on the cylindrical batteries of Examples 1-18 and Comparative Examples 1-11, and the evaluation method is as follows:

[0146] Test of the capacity retention rate after 600 cycles at 1C rate (taking the cylindrical battery with high-nickel ternary material NCM811 and graphite-mixed silicon negative electrode as an example, for other types of batteries, the test voltage range needs to be corrected).

[0147] Take a cylindrical battery, such as 21700 5Ah, place it in a constant temperature oven at 25°C for more than 4 hours, and perform tests according to the following steps:

[0148] (1) Discharge the battery at a constant current of 0.1C until it reaches a cut-off voltage of 2.5V, and let it stand for 5 minutes;

[0149] (2) Charge the battery at a constant current of 0.1C until it reaches 4.2V, and then charge it at a constant current of 0.01C until it reaches a cut-off voltage of 4.2V, and let it stand for 5 minutes;

[0150] (3) Discharge the battery at a constant current of 0.1C until it reaches a cut-off voltage of 2.5V, and let it stand for 5 minutes;

[0151] (4) Charge the battery at a constant current of 1C until it reaches 4.2V, and then charge it at a constant current of 0.01C until it reaches a cut-off voltage of 4.2V, and let it stand for 5 minutes;

[0152] (5)Discharge the battery at a constant current of 1.0C until it cuts off at 2.5V, let it stand for 5 minutes, read the capacity value C0 at this time, and then let it stand for 5 minutes;

[0153] (6)Repeat steps (4) and (5) 600 times;

[0154] (7)Obtain the cycling performance of a single battery, namely the capacity retention rate, through the ratio of the 600th discharge capacity to the first discharge capacity C0 in steps (4) and (5).

[0155] If the positive electrode of the battery is lithium iron phosphate, then change to the following test steps:

[0156] Take a cylindrical battery, such as 21700 3Ah, place it in a constant temperature oven at 25°C for more than 4 hours, and conduct tests according to the following steps:

[0157] (1)Discharge the battery at a constant current of 0.1C until it cuts off at 2.0V, and let it stand for 5 minutes;

[0158] (2)Charge the battery at a constant current of 0.1C until it cuts off at 3.6V, and then charge it at a constant voltage until it cuts off at 0.05C, and let it stand for 5 minutes;

[0159] (3)Discharge the battery at a constant current of 0.1C until it cuts off at 2.0V, and let it stand for 5 minutes, read the capacity value C0 at this time;

[0160] (4)Charge the battery at a constant current of 1.0C until it reaches 3.6V, and then charge it at a constant voltage until it cuts off at 0.05C, and let it stand for 5 minutes;

[0161] (5)Discharge the battery at a constant current of 1.0C until it cuts off at 2.0V, and let it stand for 5 minutes;

[0162] (6)Repeat steps (4) and (5) 600 times;

[0163] (7)Obtain the cycling performance of a single battery, namely the capacity retention rate, through the ratio of the 600th discharge capacity to the first discharge capacity in steps (4) and (5).

[0164] The test of the capacity retention rate after 600 cycles at 3C rate is the same as the test of the capacity retention rate after 600 cycles at 1C rate, the difference is that the charge and discharge rates in steps (4) and (5) become 3C.

[0165] The test results of the resistivity of the lithium iron phosphate positive electrode sheets and the electrochemical performance of the corresponding batteries in Examples 1 to 18 and Comparative Examples 1 to 11 are shown in Table 3.

[0166] Table 3 Test results of resistivity of lithium iron phosphate positive electrode sheets and electrochemical performance of corresponding batteries in Examples 1-18 and Comparative Examples 1-11

[0167]

[0168]

[0169] The positive electrode sheet doped with F-MWCNTs prepared by the present invention and the cylindrical battery prepared using the positive electrode sheet have a lower resistivity and a better battery capacity retention rate at different rates as can be seen from the test results in Table 2. It can be concluded from the test results in Table 2 that when the lithium ion battery uses a lithium iron phosphate positive electrode material, the resistivity R of the positive electrode sheet of the lithium ion battery is 2.2-3.7 Ω·cm, and when the lithium ion battery uses a lithium nickel cobalt manganese oxide positive electrode material, the resistivity R of the positive electrode sheet of the lithium ion battery is 0.7-1.4 Ω·cm. The capacity retention rate of the lithium ion battery after 600 cycles at 1C rate is 80-93%; the capacity retention rate of the lithium ion battery after 600 cycles at 3C rate is 82-94%.

[0170] Please refer to Figure 4 , in Comparative Examples 1-2, different types of conductive agents were selected, which was reflected in a higher resistivity than that of Example 1 using WO3 / F-MWCNTs conductive agent, and at the same time, the battery capacity retention rate at different rates was also lower than that of Example 1.

[0171] Comparing Examples 1-3 and Comparative Examples 3-5, it can be seen that too little WO3 has a poor modification effect on carbon nanotubes, and too much WO3 is not conducive to forming a more stable lattice structure, and WO3 may peel off at high rates. Therefore, the modification effect of the carbon nanotubes on the lithium iron positive electrode sheet obtained in Example 2 and Comparative Examples 3-4 is poor, which is reflected in a higher resistivity and a slightly worse capacity retention rate; while in Example 3 and Comparative Example 5, although the resistivity decreases, the capacity retention rate is lower than that of Example 1.

[0172] Comparing Examples 4-6 and Comparative Example 6, the resistivity of Example 5 is slightly lower than that of Example 1. This is because when the particle size of WO3 particles is small, it usually has a higher specific surface area, which helps to increase its contact area with carbon nanotubes (F-MWCNTs), thereby improving the conductivity of the overall composite material. However, the capacity retention rate of Example 5 is lower than that of Example 1 because small particles are prone to agglomeration, which may block the lithium ion transmission channels and cause the electrochemical performance to decline.

[0173] Comparing Examples 7-9 with Comparative Examples 7-8, it can be seen that when there is too little fluorine element, the modification effect on carbon nanotubes is poor. When there is too much fluorine element, it is not conducive to the formation of a more stable lattice structure by fluorine atoms and carbon nanotubes together. Therefore, the modification effect of the nitrogen-doped carbon nanotubes obtained in Comparative Example 7 and Comparative Example 8 on the lithium iron phosphate positive electrode sheet is poor, manifested as a slightly worse cycle capacity retention rate at high rates.

[0174] Comparing Example 1, Examples 10-11 with Comparative Examples 9-10, it can be seen that the aspect ratio of the fluorinated carbon nanotubes also has a certain impact on their performance. Using the fluorinated carbon nanotubes with an aspect ratio of 1000:1 in Example 1 is more conducive to reducing the resistivity of the lithium iron phosphate positive electrode sheet, and the discharge capacity cycle performance is better. At the same time, the resistivity of Example 11 is lower than that of Example 1, but its capacity retention rate is slightly lower. This is because the larger the aspect ratio of the carbon nanotubes, the more electron transmission paths can be provided, thereby reducing the internal resistance of the battery and improving the overall conduction efficiency. However, carbon nanotubes with a higher aspect ratio are more difficult to disperse, which may cause aggregation and affect the electrochemical performance of the electrode sheet.

[0175] Comparing Example 1, Examples 12-16, it can be seen that the selection of the fluorine source and the carbon source also has a certain impact on the performance of the finally formed F-MWCNTs. Using acetylene and nitrogen trifluoride in combination gives the best improvement effect on the conductivity and cycle performance of the lithium iron phosphate positive electrode sheet for the obtained F-MWCNTs.

[0176] Comparing Example 1, Examples 17-18, it can be seen that when the proportion of the nitrogen-doped carbon nanotubes in the lithium iron phosphate positive electrode sheet is in the range of 1-3 wt%, the conductivity, low-temperature discharge capacity, and cycle performance of the obtained lithium iron phosphate positive electrode sheet are all good.

[0177] Comparing Example 1, Examples 19-24, it can be seen that the design of this application is applicable to lithium-ion batteries with different material systems. Using high-nickel ternary materials can significantly reduce the internal resistance rate of the battery electrode sheet and improve the discharge efficiency of the lithium-ion battery.

[0178] There is no conductive agent added to the lithium iron phosphate positive electrode sheet in Comparative Example 11. The resistivity of the lithium iron phosphate positive electrode sheet in this example is significantly larger, and the corresponding capacity retention rate is lower, indicating that the presence or absence of a conductive agent has a greater impact on the conductivity and cycle performance of the lithium iron phosphate positive electrode sheet.

[0179] In summary, for the lithium-ion cylindrical battery, preparation method of composite conductive agent, multi-walled carbon nanotube, positive electrode coating, and electrical device of the present invention, by introducing tungsten trioxide into the positive electrode conductive agent, the chemical stability and cycling performance of the positive electrode material are improved. The octahedral molecular unit along the c-axis in the WO3 crystal structure is beneficial to electron conduction, which has a positive impact on the charge-discharge efficiency and power density of the battery. The continuous three- and six-ring tunnels constructed along the ab plane in the WO3 crystal structure are beneficial to ion diffusion, which helps to improve the charge-discharge rate and rate capacity retention performance of the battery; at the same time, the fast charge and discharge and long cycling performance of the battery can also be enhanced.

[0180] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the spirit and scope of the technical solutions of the present invention, and they should all be covered within the scope of the claims of the present invention.

Claims

1. A lithium-ion cylindrical battery, characterized in that, Comprising: a positive electrode sheet, a negative electrode sheet, and a separator located therebetween; the positive electrode sheet includes a positive electrode current collector and a positive electrode coating located on at least one surface of the positive electrode current collector; wherein the positive electrode coating is formed by mixing a positive electrode active material, a composite conductive agent, and a binder; the composite conductive agent includes tungsten trioxide in-situ modified fluorine-doped multi-walled carbon nanotubes; the preparation method of the composite conductive agent includes the following steps: Step S1, pretreat the substrate: Use a silicon dioxide silicon wafer as the substrate, deposit a 0.3-1 nm gold thin film layer on the substrate by thermal evaporation to obtain a gold thin film silicon wafer, and perform ethanol cleaning and heat pretreatment on it to obtain a pretreated substrate; Step S2, synthesize fluorine-doped multi-walled carbon nanotubes: Select a catalyst, introduce a carbon source while introducing a fluorine source as a doping source; at the same time, control the flow rates of the carrier gas and the carbon source gas; control the growth time of the carbon nanotubes, take out the carbon nanotubes grown on the pretreated substrate, obtain a suspension through pickling and ultrasonic treatment, and then filter, wash, and dry the suspension to obtain fluorine-doped multi-walled carbon nanotubes; Step S3, in-situ grow tungsten trioxide WO3 metal nanoparticles inside the carbon nanotubes: Mix the metal alkoxide precursor with a solvent, heat and stir to promote the hydrolysis reaction of the metal alkoxide, and obtain a sol after hydrolysis is completed. Add the fluorine-doped multi-walled carbon nanotubes to the sol; Remove most of the solvent to form a dry gel; the dry gel is heat-treated at a high temperature to promote the final crystallization and growth of tungsten trioxide WO3 particles to obtain tungsten trioxide in-situ modified fluorine-doped multi-walled carbon nanotubes; the metal alkoxide precursor is tetrabutyl tungstate or ethyl tungstate; the mass ratio of the fluorine-doped multi-walled carbon nanotubes to the tungsten trioxide is 95:5 to 90:

10.

2. The lithium-ion cylindrical battery according to claim 1, wherein the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate.

3. The cylindrical lithium-ion battery according to claim 2, wherein the lithium nickel cobalt manganese oxide material includes one or more of a high-nickel ternary lithium nickel cobalt manganese oxide material or a medium-nickel ternary lithium nickel cobalt manganese oxide material; The chemical formula of the medium-nickel ternary lithium nickel cobalt manganate material is Li a Ni x Co y Mn z M b O2, where 0.9 < a < 1.1, 0.4 ≤ x ≤ 0.7, 0.1 ≤ y < 0.4, 0.05 ≤ z < 0.4, 0 ≤ b ≤ 0.1, and M is any one or a combination of more than one of Al, Mg, Zr, Ti, W, Nb, Mo, and B.

4. The lithium-ion cylindrical battery according to claim 1, wherein, the cylindrical lithium-ion battery satisfies at least one or more of the following conditions: (1) The average particle size Dv50 of the tungsten trioxide is 9-60 nm; (2) The molar ratio of tungsten trioxide in the positive electrode sheet to silicon in the negative electrode sheet is n(WO3) / n(Si)=0.01-0.05; (3) The resistivity R of the positive electrode sheet is 0.7-3.7 Ω*cm; (4) The mass fraction of fluorine element in the composite conductive agent is 0.5-1.5%; (5) The aspect ratio of the multi-walled carbon nanotubes in the composite conductive agent is (600-1400):

1.

5. The cylindrical lithium-ion battery according to claim 1, wherein it further includes a negative electrode coating; the negative electrode coating includes a negative electrode active material, a conductive agent, and a binder; wherein the negative electrode active material includes at least two of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-carbon material, and silicon-oxygen material mixed, and the silicon content in the negative electrode active material is 5-40 wt%.

6. The lithium-ion cylindrical battery according to claim 5, characterized in that, The negative electrode active material is a graphite negative electrode with a high silicon content, and the molar ratio of tungsten trioxide in the positive electrode sheet to silicon in the negative electrode sheet is n(WO3) / n(Si) = 0.01 - 0.

02.

7. The lithium-ion cylindrical battery according to claim 1, wherein, The diameter of the lithium-ion cylindrical battery is 30 - 50 mm, and the height is 70 - 180 mm; and the ratio of the height to the diameter is greater than 1.

6.

8. The lithium-ion cylindrical battery according to claim 1, wherein The catalyst is a transition metal and its oxides or carbides, including any one or more of iron, cobalt, and nickel; The carbon source includes any one or more of methane, acetylene, ethylene, and carbon monoxide; The fluorine source includes any one or more of fluorine gas, nitrogen trifluoride, and carbon tetrafluoride; The carrier gas is nitrogen.

9. The lithium-ion cylindrical battery according to claim 1, wherein, In the step S1, it further includes: Cleaning the silicon dioxide wafer by ultrasonic cleaning and chemical treatment to remove surface contaminants; and The thermal evaporation method is specifically: placing a gold material with a purity of 99.99% on an electron beam heater, heating it to 1100 - 1300 °C to evaporate gold and deposit it on the cleaned silicon dioxide wafer; The ethanol cleaning and heating pretreatment is specifically: immersing the gold thin film silicon wafer in ethanol, ultrasonically cleaning for 3 - 5 minutes, and heating it to 170 - 210 °C in a nitrogen atmosphere and maintaining it for 8 - 15 minutes to remove ethanol residues and activate the surface; The vacuum degree of the deposition environment is 80 - 100 kPa.

10. The lithium-ion cylindrical battery according to claim 1, wherein, In the step S2: The pickling is specifically: pickling the grown carbon nanotubes with a dilute hydrochloric acid solution to remove residual catalysts; The ultrasonic treatment is specifically: ultrasonically treating for 25 - 35 minutes to disperse the carbon nanotubes; The filtration, washing, and drying are specifically: filtering the suspension with a polytetrafluoroethylene filter, then washing with deionized water, and drying the carbon nanotubes at 60 - 80 °C for 10 - 12 hours.

11. An electrical device, characterized in that, It includes the lithium-ion cylindrical battery according to any one of claims 1 - 10.

Citation Information

Patent Citations

  • High-rate lithium-ion battery

    CN107579253A